OPEC in the 21st century. What has changed and what have we learned? - Merino Garcia, P (Oxford Institute for Energy Studies, 2005)
OPEC was founded in 1960. Looking back, it is hard to detect a constant pattern guiding its actions and policies over these forty years. Probably its only constant strategy has been to adapt to changing conditions in the relationship between economic growth, oil product demand, oil prices and the supply response. Its reaction has always been slow, but this is largely because it has always been difficult to predict changes or even be sure that these have in fact occurred. The first question we need to ask when trying to analyse OPEC policies is, ‘What is OPEC’s mission?’ If we look carefully at OPEC’s resolutions, the objective mentioned most often is that of ‘attaining price stability’. Yet, although this is one of the goals for which the organisation was founded, success seems to become more and more elusive, and, today, price is as volatile as it ever has been.